2015
DOI: 10.1111/1440-1681.12384
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates asthmatic airway inflammation by activating nuclear factor‐E2‐related factor 2/haem oxygenase (HO)‐1 signalling pathway

Abstract: Previous studies have shown that curcumin alleviates asthma in vivo. However, the relationship between curcumin and the nuclear factor-E2-related factor 2 (Nrf2)/haem oxygenase (HO)-1 pathway in asthma treatment remains unknown. The aim of the present study was to investigate the mechanisms of curcumin involved in the amelioration of airway inflammation in a mouse asthma model. Curcumin was administrated to asthmatic mice, and bronchoalveolar lavage fluid was collected. Inflammatory cell infiltration was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 53 publications
(98 reference statements)
2
28
0
Order By: Relevance
“…There are several mechanisms described for CUR derivatives to exercise their antiinflammatory activity. Liu et al (2015), reported that derivatives of CUR might alleviate airway inflammation in asthma through the Nrf2/HO-1 pathway. Other studies suggest that intranasal CUR (2.5 and 5.0 mg/ kg) regulates airway inflammation and airway obstruction by modulating cytokine levels (IL-4, IL-5, IFN-α, and TNF-α) and sPLA2 activity thereby inhibiting PGD 2 release and COX-2 expression (Kumari, Dash, & Singh, 2017;Masella, Di Benedetto, Varì, Filesi, & Giovannini, 2005;Subhashini, Chauhan, Dash, Paul, & Singh, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are several mechanisms described for CUR derivatives to exercise their antiinflammatory activity. Liu et al (2015), reported that derivatives of CUR might alleviate airway inflammation in asthma through the Nrf2/HO-1 pathway. Other studies suggest that intranasal CUR (2.5 and 5.0 mg/ kg) regulates airway inflammation and airway obstruction by modulating cytokine levels (IL-4, IL-5, IFN-α, and TNF-α) and sPLA2 activity thereby inhibiting PGD 2 release and COX-2 expression (Kumari, Dash, & Singh, 2017;Masella, Di Benedetto, Varì, Filesi, & Giovannini, 2005;Subhashini, Chauhan, Dash, Paul, & Singh, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…7c,d). The expression of HO-1 is regulated by Nrf24849 and CUR activates this signaling pathway. Whole genome expression profiling unraveled that oral CUR feeding regulates more than 800 NRF2-dependent genes in vivo with a >2-fold induction or suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 has been shown to be protective in various inflammatory animal models (Cho et al, 2013;Liu et al, 2015;Rangasamy et al, 2005). Importance of Nrf2 is also strengthened by the fact is that its induction leads to transcription of many antioxidant genes which include hemeoxygenase 1, glutathione peroxidase and SOD (Eggler et al, 2008;Lee et al, 2008;Vijayan et al, 2011;Zhu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a transcription factor that is activated by ROS and responsible for detoxification through induction of various antioxidant genes (Lee and Yang, 2012;Liu et al, 2015;Spiess et al, 2013;Yao et al, 2007). One of the antioxidants that may be induced through Nrf2 is superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%